The Paratextual Labeling of Autistic-Authored YA Fiction as #OwnVoices: How YA Literary Culture Creates Space for Neurodivergent Authorship - Jason Michael Abad (Disability Studies Quarterly, 2021)
This essay considers the effect of #OwnVoices on autistic literary representation by analyzing how autistic authors use paratexts to prescribe for some readers ways of understanding autistic-authored texts while temporarily refraining from prescribing a particular method for others, allowing readers with opposing ideologies to first read the narrative before they encounter the more didactic elements of the text. Building on Gerrard Genette's theorization of the paratext, this essay compares the use of text and paratext in two works of autistic-authored fiction, Corinne Duyvis's On the Edge of Gone and Jen Wilde's Queens of Geek, to that of Mark Haddon's The Curious Incident of the Dog in the Night-Time, a work of allistic-authored YA fiction. The contrast between these two kinds of texts reveals how #ownvoices texts foreground the positionality of the author in ways that enable rather than foreclose discussions about the ethical representation of autistic people.
Keywords: #OwnVoices; Autism; Autistic Authorship; Literary Representation; Paratext; Literary Theory